2006
DOI: 10.1002/ajp.20361
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic evaluation of neonatal skeletal development inCallimico goeldiireveals closer similarity toCallithrix jacchusthan toSaguinus oedipus

Abstract: The phylogenetic affinities of the neotropical Goeldi's monkey (Callimico goeldii) have long been a matter of debate. Whereas most morphological evidence appears to place Callimico in a sister group position relative to the Callitrichidae, genetic studies place C. goeldii within the Callitrichidae and suggest that it is more closely related to marmosets than to tamarins. The present study presents the first radiographic analysis comparing the secondary limb bone ossification of newborn C. goeldii with represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…This hypothesis, however, has little to no morphological support (Schneider and Rosenberger, 1996;Porter and Garber, 2004). Only recently have Hofmann et al (2007) reported the first morphological evidence for a sister group relationship between Callimico and Callitrichini, based on the ossification pattern of the long bone epiphyses and of the carpal/metacarpal and tarsal/metatarsal short bones. However, a sampling bias, stated by the authors themselves, is evident in the work, as no specimens of Leontopithecus were sampled.…”
Section: Marmoset Interrelationshipsmentioning
confidence: 99%
“…This hypothesis, however, has little to no morphological support (Schneider and Rosenberger, 1996;Porter and Garber, 2004). Only recently have Hofmann et al (2007) reported the first morphological evidence for a sister group relationship between Callimico and Callitrichini, based on the ossification pattern of the long bone epiphyses and of the carpal/metacarpal and tarsal/metatarsal short bones. However, a sampling bias, stated by the authors themselves, is evident in the work, as no specimens of Leontopithecus were sampled.…”
Section: Marmoset Interrelationshipsmentioning
confidence: 99%
“…Shape variables may also influence the observed sequence; these include sexual dimorphism (Garn et al, 1966) and adult morphology (Haluska and Alberch, 1983;Adams, 1992;Rieppel, 1993). Additionally, phylogeny (Maisano, 2002;Poe, 2006;Hofmann et al, 2007), adaptations to postembryonic life (Adriaens and Verraes, 1998;Mabee et al, 2000;Sá nchez-Villagra, 2002;Prochel, 2006), life-history (Prochel 2006), and other untested ecological variables such as temperature, humidity, and geography result in variation both between and within species (Sheil and Greenbaum, 2005). Some or all of these factors may affect the observed sequence, and can be difficult to isolate as they often interact and influence one another.…”
mentioning
confidence: 98%
“…For example, delayed embryonic development is present in C. goeldii and the other twinning callitrichids, a trait not found in other platyrrhines (Oerke et al 2002). C. goeldii neonates also show a pattern of secondary limbbone ossification more similar to the pattern observed in C. jacchus than to Saguinus or other platyrrhines (Hofmann et al 2007). Phylogenies based on molecular evidence place C. goeldii as the sister taxa to C. jacchus (Horovitz and Meyer 1997;Pastorini et al 1998;Claridge et al 1999;von Dornum and Ruvolo 1999).…”
Section: Introductionmentioning
confidence: 92%